1983
DOI: 10.1136/gut.24.8.761
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone related blood volume expansion in cirrhosis before and during the early phase of ascites formation.

Abstract: SUMMARY Thirty-seven patients with liver cirrhosis (16 without ascites: group 1; 21 with untreated ascites at the first onset: group 2) were studied during controlled sodium intake (40 mmol/day). Renal plasma flow, glomerular filtration rate, urinary sodium excretion, plasma sodium and potassium, plasma renin activity, plasma aldosterone concentration, blood volume, and arterial pressure were evaluated. All the patients had normal renal perfusion, plasma sodium and potassium, and arterial pressure. Mean plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1
4

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 19 publications
5
38
1
4
Order By: Relevance
“…Aldosterone is considered an important hormone in the sodium retention of cirrhotic patients [1], In cirrhotics without fluid retention, plasma aldosterone concentra tion and urine aldosterone excretion, expressed as a function of urine sodium excretion, are reduced [2][3][4]. Moreover, only one third of the patients with ascites and without renal failure have an activated renin-angiotensin-aldosterone system [3].…”
Section: Introductionmentioning
confidence: 99%
“…Aldosterone is considered an important hormone in the sodium retention of cirrhotic patients [1], In cirrhotics without fluid retention, plasma aldosterone concentra tion and urine aldosterone excretion, expressed as a function of urine sodium excretion, are reduced [2][3][4]. Moreover, only one third of the patients with ascites and without renal failure have an activated renin-angiotensin-aldosterone system [3].…”
Section: Introductionmentioning
confidence: 99%
“…23 To reconcile these findings, it has been proposed that aldosterone sensitivity was increased in cirrhosis. [24][25][26][27] This apparent high sensitivity to aldosterone might be accounted for in fact by the abnormal activation of MR by glucocorticoids. Supporting this hypothesis was the finding that 11␤ hydroxysteroid dehydrogenase type 2 (11␤ -HSD2) activity, which prevents access of glucocorticoids to MRs, 28 is decreased in cirrhosis.…”
mentioning
confidence: 99%
“…In this con text, Bernardi et al [14] recently demonstrated that renin and plasma aldosterone were not elevated in cir rhotic patients. Studies by Sellars et al [15] showed that the renin-aldosterone system is not activated in un treated, decompensated cirrhosis with established as cites.…”
Section: Discussionmentioning
confidence: 99%